2021
DOI: 10.1097/inf.0000000000003263
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and Tolerability of Monoclonal Antibody Therapies for Treatment of COVID-19 in Pediatric Patients

Abstract: There is a little data regarding safety or efficacy of monoclonal antibody treatment for mild-to-moderate COVID-19 in pediatric patients despite it being frequently used in adults. This retrospective study of 17 patients with mild-to-moderate COVID-19 who received monoclonal antibody therapy found that the treatment was well tolerated, safe, and may be effective in halting progression to severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…In clinical studies, SARS-CoV-2 monoclonal antibodies reduced hospitalization and mortality in patients with mild and moderate COVID-19 who had risk factors for progression to severe COVID-19 [ 44 - 47 ]. Mak et al [ 48 ] reported that monoclonal antibody treatment appeared to be safe and effective in some child and adolescent COVID-19 patients.…”
Section: Anti-sars-cov-2 Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical studies, SARS-CoV-2 monoclonal antibodies reduced hospitalization and mortality in patients with mild and moderate COVID-19 who had risk factors for progression to severe COVID-19 [ 44 - 47 ]. Mak et al [ 48 ] reported that monoclonal antibody treatment appeared to be safe and effective in some child and adolescent COVID-19 patients.…”
Section: Anti-sars-cov-2 Monoclonal Antibodiesmentioning
confidence: 99%
“… SARS-CoV-2 monoclonal antibodies authorized for COVID-19 treatment in children and adolescents [ 48 ] …”
Section: Supplementary Materialsmentioning
confidence: 99%
“…There is a paucity of data on the efficacy and tolerability of MCA therapy in pediatric patients as little research has been conducted in this patient population. Mak and colleagues recently published their experience using MCA therapy in 17 pediatric patients and reported that treatment was well-tolerated and may be effective in limiting progression to more severe disease, though this is the first preliminary report published in this area [20].…”
Section: Introductionmentioning
confidence: 99%
“…In May 2021, a group of experts, based on the evidence, suggested that routine administration of mAb therapy for treatment of COVID-19 in children or adolescents was not permissible [20]. Yet, a recent report by Mak et al showed a case-series of 17 patients with ages between 12 and 20 years old with COVID-19, who were treated with mAbs (bamlanivimab, bamlanivimab-etesevimab, casirivimab-imdevimab) [21] and the treatment was well-tolerated and safe, with no adverse reactions reported. To support this evidence, we report our experience of the administration of mAb as a treatment for COVID-19 in pediatric patients aged from 24 days to 18 years old.…”
Section: Introductionmentioning
confidence: 99%